Early Hypocalcemia after Sub-Total, Near-Total and Total Thyroidectomy: its Diagnosis and Treatment Options - Tahir Hamid, Amir Usman, Saqib Uddin Khan, Ahmad Raza Nasr, Javeria Usman, Mansab Ali, Javed Rafique Maliki (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Hypocalcemia after thyroid surgery is most important and early complication1. The main aim of this study is to diagnose early hypocalcemia after thyroid surgery and its treatment options Method: 100 patients fulfilling inclusion criteria from December 2018 to February 2021 were included in this study who had undergone thyroid surgery (sub-total, near-total and total). Serum calcium less than 8.1 mg/dl, measured after 24 hours to 48 hours of surgery is taken as hypocalcemia. Following variables are assessed in this study, gender, age, pre-operative serum calcium levels and type of surgery. Hypocalcemia diagnosed by post-operative serum calcium levels, presence of numbness, Chvostek’s sign or Trousseau’s sign noted and analyzed by SPSS v20 was used for statistical analysis. p-value less than 0.05 was considered as statistically significant. Results: Early post-hypocalcemia developed in 71 (71%) patients of them 13(18%) were males and 58 (82%) were females and female gender is significantly more associated with hypocalcemia (p=0.001) Type of surgery (sub-total, near-total and total) is not related to development of early hypocalcemia (p=0.169). Patients who developed early hypocalcemia divided into two groups- A and B respectively. Group A is treated with oral calcium alone and B with oral calcium combined with Vitamin D3. The patients followed up for 6 months. The patients who treated with oral calcium and vitamin D3 combined responded well as compares with oral calcium alone (p=.001). Conclusion: This study suggests that female gender is associated with early hypocalcemia however there is no significant different type of surgery and patients who treated with oral calcium combined with vitamin D3 responded well as compared with oral calcium alone.